Antibiotic Prophylaxis In Preventing Surgical Site Infection In Patients Undergoing Lichtenstein’s Hernioplasty - Rizwanullah Junaid Bhanbhro; Khalil Ahmed Almani; Sadia Kazi (Journal of Bahria University Medical and Dental College)
Objective: To determine the antibiotic prophylaxis in preventing surgical site infection in patients undergoing Lichtenstein’s hernioplasty. Study design: Observational study Place and Duration: Department of surgery, ISRA University Hospital, Hyderabad. from December 2015 to March 2017. Materials and Methods: 120 cases of inguinal hernia planned for Lichtenstein’s hernioplasty were selected according to exclusion criteria and divided into control and antibiotic group. Pre- operative patient history, physical examination and inguinal hernia examination was performed. Prophylactic antibiotic ceftriaxone (1000 mg) was given over night of surgical procedure. Statistical software SPSS 21.0 was used for data analysis at 95% CI (P <0.05). Results: Mean± SD age was noted as 39.51 ± 7.56 years (15 – 61 years). Of 120, who underwent Lichtenstein’s hernioplasty the direct and indirect hernias were noted in 35 (29.16%) and 33 (27.5%) & 25 (20.83%) and 27 (22.5%) of control and antibiotic groups respectively. Of 120 subjects, the SSI was noted in 17 (14.1%) in control and 5 (4.16%) in antibiotic group. Cumulative SSI in 120 cases was 22 (18.33%). Conclusion: The present study reports low incidence of surgical site infection with antibiotic prophylaxis in Lichtenstein’s mesh repair in open inguinal hernioplasty. Key words: Antibiotic Prophylaxis, Surgical